Shirley Jackson papers - Jackson, Shirley, 1916-1965.
Correspondence; diaries; journals; manuscripts, typescripts, and galleys of articles, books, and short stories; notes; college notebooks; Hyman and Jackson family papers; watercolors; pencil and ink drawings; and other papers pertaining primarily to the development of Jackson's novels and short stories as well as to her supernatural tales and to her humorous stories about contemporary domestic life. Family correspondents include Jackson's husband, Stanley Edgar Hyman, and her parents, Leslie H. Jackson and Geraldine B. Jackson. Other correspondents include Walter Bernstein; Jean Brockway; Elizabeth "Libby" Batterham Burke; John Ciardi; Pascal Covici; Carol Black Livaudais; June Mirken Mintz; Frank Orenstein; Louis L. Scher; Mary Shaw; Robert M. Strauss; Louis Untermeyer; Jay Williams; the publishing firm of Farrar, Straus and Young; and Jackson's literary agents, Brandt & Brandt and the Music Corporation of America.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Smithsonian Institution.
Author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Material was transferred to this collection from the Manuscript Division's Stanley Edgar Hyman papers.
Keywords: Bernstein, Walter -- Correspondence; Brockway, Jean -- Correspondence; Burke, Elizabeth Batterham -- Correspondence; Ciardi, John, -- 1916-1986 -- Correspondence; Covici, Pascal, -- 1930- -- Correspondence; Hyman, Stanley Edgar, -- 1919-1970 -- Correspondence; Jackson, Geraldine B. -- Correspondence; Jackson, Leslie H. -- Correspondence; Livaudais, Carol Black -- Correspondence; Mintz, June Mirken -- Correspondence; Orenstein, Frank -- Correspondence; Scher, Louis L. -- Correspondence; Shaw, Mary -- Correspondence; Strauss, Robert M. -- Correspondence; Untermeyer, Louis, -- 1885-1977 -- Correspondence; Williams, Jay, -- 1914-1978 -- Correspondence; Hyman family; Jackson family; Brandt & Brandt -- Correspondence; Farrar, Straus and Young -- Correspondence; Music Corporation of America -- Correspondence; American fiction; Fiction; Horror tales, American; Humorous stories, American; Short stories, American; Supernatural in literature; Authors